The Influence of Perceived Digital Marketing Capability on Technology Adoption in Secondary Schools: Evidence from Jabodetabek - Agung Wijoyo (Lembaga Penelitian Universitas YARSI, 2026)
This study examines the role of Perceived Digital Marketing Capability (PDMC) as an organizational antecedent of Technology Adoption (TA) among secondary school teachers, using an extended Technology Acceptance Model (TAM) with serial mediation through Perceived Ease of Use (PEOU) and Perceived Usefulness (PU). PDMC is defined as perceived operational digital capability, reflecting how internal stakeholders experience the organization’s use of digital platforms. Data were collected through a cross-sectional survey of 350 teachers from 35 secondary schools in the Jabodetabek region and analyzed using PLS-SEM with bootstrapping (5,000 subsamples). Results indicate that PDMC significantly influences PEOU (β = 0.498, p < 0.001) and PU (β = 0.129, p = 0.017), while PEOU significantly affects PU (β = 0.447, p < 0.001). PU significantly predicts TA (β = 0.407, p < 0.001), whereas the direct effects of PDMC and PEOU on TA are not significant. The model explains 18.1% of the variance in TA (R² = 0.181). Mediation analysis confirms that PU fully mediates the PDMC–TA relationship. These findings suggest that technology adoption is primarily driven by perceived usefulness, highlighting the importance of perceived digital capability in shaping user perceptions.